Trend in Ambient Ozone and an Attempt to Detect Its Effect on Biota in Forest Ecosystem. Step I of Lithuanian Studies - Algirdas Augustaitis; Ingrida Augustaitiene; Almantas Kliucius; Gintautas Mozgeris; Gintaras Pivoras; Rasele Girgzdiene; Kestutis Arbaciauskas; Irena Eitminaviciute; Reda Mazeikyte (The Scientific World Journal)
The presented study aimed to explore the relationships between ambient ozone (O3) and tree defoliation, specific diversity, and abundance of soil microarthropods, stream macroinvertebrates, and small mammals (mainly rodents) in order to test the hypothesis that changes in the considered objects of the forest ecosystem could be related to changes in ambient O3, concentration of which is below critical level. The observations were carried out from 1994 at three integrated monitoring stations. The obtained data revealed that only peak O3 concentrations (from 125–215 μg·m-3) had significant effect on changes in the considered components of forest biota.